In‐Flight Calibration of Near‐Infrared Reflectance Spectra Measured by the Zhurong Mars Rover. Issue 2 (11th February 2023) - Lin, Honglei; Xu, Rui; Lin, Yangting; Xu, Xuesen; Wu, Bing; Gou, Sheng; Wei, Yong
Abstract: The Zhurong rover of the China's first Mars Exploration Mission successfully landed on the northern plain of Mars and measured near‐infrared (NIR) reflectance spectra with the Mars Surface Composition Detector (MarSCoDe). There was only orbital NIR hyperspectral data before the success of the Zhurong and Perseverance rovers in 2021. The in situ spectral measurements by the rover face different problems when compared with orbital measurements in data analysis, and thus need a new process pipeline. We analyzed the factors affecting the quality of the NIR spectra acquired by the Zhurong rover, including temperature variation of the detector, non‐homogeneous properties of the calibration panels, the atmosphere transmission and Martian dust buildup on the calibration panels. We then identified that the Martian dust buildup on the calibration panels is the main factor affecting the spectra, causing significant discrepancies between the reflectance calibrated with the white and gray panels, respectively, and the systematically higher reflectance values of the Martian soils measured by the Zhurong rover than those by other missions. We proposed a spectral unmixing strategy to restore the radiance of clean calibration panels on the rover and then derived the reflectance spectra with an uncertainty of ∼14%. The method has been tested by simulation experiments in laboratory. The data quality of the in situ NIR spectra of the Zhurong rover is significantly improved after the calibrations based on our pipeline, which is critical for mineral identification on small scales and calibrations of the orbital remote sensing data. Plain Language Summary: The Zhurong rover successfully landed on the shoreline‐like boundaries in the northern lowlands of Mars, and has the capability of exploring the compositions there using near‐infrared reflectance spectra. This is the first attempt to obtain the in situ hyperspectral reflectance data of surface in the northern lowlands. So, the accurate data is very critical for compositional analysis, which provide an unprecedented opportunity to explore if the ancient ocean existed or not. We systematically analyzed the factors on the quality of in situ measured spectra and built a data process pipeline, which lays the foundation for the massive data analysis of the Zhurong rover. Key Points: The Zhurong rover in situ measured the near‐infrared hyperspectral reflectance data of surface in the northern lowlands of Mars for the first time The Martian dust buildup on the calibration panels significantly affect the shapes and intensities of reflectance spectra of Martian surface A data process pipeline for near‐infrared reflectance spectra acquired by the Zhurong rover is built